Xanthogranulomatous Epididymitis Unresponsive to Antibiotic Treatment - Yeasol Kwon; Jun Baek Park; Sang Hwa Lee; Seung Ki Min (Urogenital Tract Infection)
Xanthogranulomatous epididymitis is very rare, and there are few case reports worldwide. Clinically, it is necessary to differentiate between chronic scrotal inflammatory diseases, such as tuberculous epididymitis and testicular tumors. Proteus and Escherichia coli are the pathogens that generally cause xantho-granulomatous pyelonephritis, but the pathogens of xanthogranulomatous epididymitis are unclear. This paper reports a case of a 66-year-old male with epididymitis on scrotal ultrasonography and had Pseudomonas aeruginosa detected in a culture test. An orchiectomy was performed because he did not respond to antibiotic treatment.